His vanished star - Craddock, Charles Egbert, 1850-1922 (Salt Lake City, UT : Project Gutenberg, 2025)
"His Vanished Star" by Charles Egbert Craddock is a novel written in the late 19th century. Set in the American South, the story revolves around the conflict between Kenneth Kenniston, a city-bred architect with ambitious development plans, and the rural Tems family who reside on the land he seeks to transform. The book likely explores themes of progress versus tradition, the clash of cultures, and the complexities of rural mountain life through the interactions of Kenniston, the Tems family, and the people of the surrounding community. The opening of the novel introduces Kenneth Kenniston as he surveys his large but sparsely valued mountainside property, envisioning a grand hotel that will attract summer visitors yet encountering practical and interpersonal obstacles. His chief concern is the presence of the Tems family, especially the patriarch "Cap'n Lucy" Tems, whose cabin lies in the middle of Kenniston$1 (Bs planned development and who stubbornly refuses to move despite offers. Scenes inside the Tems household reveal a family marked by strong personalities and deep connection to the land. As night falls, other local characters, including the enigmatic Lorenzo Taft and a covert group of moonshiners, are introduced, demonstrating the region's insular, self-sufficient society and the potential for simmering conflict over land and change. Tensions arise between commercial progress, the defense of home and autonomy, and the hidden worlds that operate beneath the surface of rural mountain life. (This is an automatically generated summary.)s
Release date is 2025-03-21
Peter Becker, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Alcohol trafficking -- Fiction; Mountain life -- Tennessee -- Fiction